Neuroprotective peptides in Alzheimer's disease:structural characterization an affinity of ß-amyloid and human cystatin C peptides interactions - Almeida, Ana (2009)
Tese de mestrado, Biologia (Biologia Humana e Ambiente), 2009, Universidade de Lisboa, Faculdade de Ciências